Аэровоздушные геоэлектрические исследования на Костанайской нефтегазоперспективной площади в Республике Казахстан - Левашов, С.П.; Якимчук, Н.А.; Корчагин, И.Н.; Жулдаспаев, М.Д.; Якубовский, В.И.; Божежа, Д.Н. (Видавничий дім "Академперіодика" НАН України, 2008)
The results of geoelectric studies within limits of the oil-gas Kostanaiskaya area are given. Practically all “deposit” type anomalies (DTA) are revealed and mapped from an aircraft. The mapped geoelectric anomalies are authenticated by the overland FSPEF survey. The intervals of position of anomalously polarized layers of the “oil” type are determined within the anomalies by VERS soundings. To construct a structural model of the area, the detailed soundings were conducted within “Kosagal” DTA for scheduling the project of the prospecti ng borehole boring.The place for a borehole is recommended.